Psychedelic New York : a history of LSD in the city - Elcock, Chris (Intoxicating histories ;, 2023)
"As LSD moves towards the medical mainstream, it continues to evoke powerful memories of the psychedelic sixties and west coast counterculture. In this lively account, Chris Elcock follows a different branch of psychedelic history--one that is sprawling, layered, and centred on New York City. A major hub for the production and consumption of LSD and other hallucinogenic drugs, New York spawned a unique psychedelic culture that reverberated through the city, from psychoanalytic circles to artists' studios, Greenwich Village to Central Park. Based on years of archival research, interviews with former acid heads, and a range of cultural artifacts, Psychedelic New York shows how the postwar city was at the forefront of LSD medical research, the burgeoning of psychedelic art, drug-accompanied spiritual seeking, and a proliferation of drug subcultures. Elcock recounts stories of New Yorkers such as Holocaust survivor Nina Graboi and artist Isaac Abrams, whose lives were dramatically altered by their psychedelic experiences, while offering new insights into Timothy Leary's role in turning on the city with psilocybin. Enlivened by personal stories and rooted in thoughtful analysis, Psychedelic New York is a multifaceted history of LSD and the urban psychedelic experience."--